Pengaruh Pemberian Pupuk Organik Cair (POC) Batang Pisang (Musa paradisiaca L) Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L): The Effect of Applying Liquid Organic Fertilizer to Banana Sticks (Musa paradisiaca L) on Growth and Yield Lettude Plant (Lactuca sativa L) - Saib, Abdul Ahmad; Laode, Bahidin; Ramlan, Winarto (Universitas Muhammadiyah Luwuk, 2024)
ABSTRACT The aim of this research was to determine the effect of giving banana stem POC concentrations on lettuce growth and yield and the optimal concentration for lettuce growth and yield. This research was carried out from July to September 2024 on the ALE'TO park land of the Food Crops, Horticulture and Plantation Service, Banggai Regency, Central Sulawesi Province. This research used a non-factorial completely randomized design method, namely the POC concentration of banana stems consisting of four treatments, namely, P0 (without giving POC), P1 (100ml), P2 (200ml) and P3 (300ml). The observation variables in this research were plant height, number of leaves, leaf area and wet weight. The research results showed that banana stem POC concentration had a significant effect on the variable plant height at 2 WAP and had a very significant effect on the variables plant height at 3 WAP, 4 WAP, 5 WAP, number of leaves, leaf area and wet weight. Treatment P3 (300ml) gave the best average value for the observation variables of plant height, number of leaves, leaf area and wet weight. The results of the research can be concluded that the POC concentration of banana stems has a real influence on the growth of lettuce at 2 WAP, and has a very real influence on the growth of plant height at 3 WAP, 4 WAP, 5 WAP, number of leaves, leaf area and wet soil and the optimal concentration is found at P3 treatment (300ml), this gave the best influence on all observed variables. Keywords: Liquid Organic Fertilizer (POC), Banana stems, Lettuce Plants